UPLC-QToF-ESI-MS identification and anthelmintic activity of Mitragyna inermis (Willd.) Kuntze (Rubiaceae) - Placide Mahougnan Toklo; Géorcelin G. Alowanou; Steven Collins N. Wouamba; Fidèle M. Assogba; Mathias A. Ahomadegbe; Amoussatou Sakirigui; Bruno Ndjakou Lenta; Sylvie Hounzangbe-Adote; Simeon Fogue Kouam; Eléonore C. Yayi-Ladekan; Joachim Djimon Gbenou (Heliyon, 2023)
Medicinal plants attract the attention of many researchers to find natural and safe remedies for various resistant diseases. Leaves of Mitragyna inermis are widely used in traditional veterinary medicine for the treatment of gastrointestinal strongyles of small ruminants. The aim of the current study is to estimate the antioxidant, anthelmintic and the larval toxicity of the aqueous and hydroethanolic extracts of this plant in addition to the hexane, dichloromethane and ethanol fractions of the hydroethanolic extract. Investigation of the most active extract using Ultra Performance Liquid Chromatography coupled with Quadrupole Time-of-Flight Electrospray Ionization Mass Spectrometry (UPLC-QToF-ESI-MS). Both plant extracts showed good antioxidant activity by scavenging the 2,2′-diphényl-1-picrylhydrazyl (DPPH) radical and reducing the ferric ion. Similarly, they were no-toxic to Artemia salina larvae (CL50 > 0.1 μg/mL). Also, they significantly reduced larval migration and motility of Haemonchus contortus adult worms (p < 0.001). The hexane, dichloromethane and ethanolic fractions of the hydroethanolic extract showed low activity compared to crude extracts except for the hexane fraction on H. contortus adult worms (p < 0.001) while it showed a poor result on larvae. It thus appears that the anthelmintic activity of the extract may be linked to the synergistic action of these compounds. The UPLC-QToF-ESI-MS analysis revealed the tentative identification of 15 compounds including 7 alkaloids. The results of the present study confirm the anthelmintic activity of M. inermis in traditional veterinary medicine.